2015
DOI: 10.1063/1.4939024
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the electron sheath and presheath

Abstract: Electron sheaths are commonly found near Langmuir probes collecting the electron saturation current. The common assumption is that the probe collects the random flux of electrons incident on the sheath, which tacitly implies that there is no electron presheath and that the flux collected is due to a velocity space truncation of the electron velocity distribution function (EVDF). This work provides a dedicated theory of electron sheaths, which suggests that they are not so simple. Motivated by EVDFs observed in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(101 citation statements)
references
References 43 publications
6
94
1
Order By: Relevance
“…This is the same expression as was obtained for the ion sheath thickness in equation (13). It is over twice as large as what is obtained based on the random flux model [19]. Simulation results are consistent with equation (35), as shown in figure 19.…”
Section: Steady-state Propertiessupporting
confidence: 86%
See 3 more Smart Citations
“…This is the same expression as was obtained for the ion sheath thickness in equation (13). It is over twice as large as what is obtained based on the random flux model [19]. Simulation results are consistent with equation (35), as shown in figure 19.…”
Section: Steady-state Propertiessupporting
confidence: 86%
“…In this case, the electron current lost to the electrode is conventionally thought to be the random thermal flux incident on the electrode eΓ e,th A E , representing a half-Maxwellian electron velocity distribution function at the electron sheath edge. However, recent work has shown the existence of an electron presheath, which establishes a flow shift of the electron distribution function by the sheath edge that satisfies an electron sheath analog of the Bohm criterion: V e = T e /m e ≡ v e,B [18,19]. Further 2D-3V PIC simulations revealed that both a combination of flow-shift and loss cone distribution contribute to the electron flux [16].…”
Section: Geometric Considerationsmentioning
confidence: 97%
See 2 more Smart Citations
“…A laboratory example of an electrostatically confined pure electron plasma, called an electron sheath, is formed at the plasma interface of a positively charged surface (Scheiner et al, ). As described herein, two key features differentiate the presently studied electron cloud from an electron sheath: (i) The electron cloud can be much larger than the typical Debye length scale for plasma charge separation, and (ii) the electron cloud produces a negative floating potential at the surface.…”
Section: Introductionmentioning
confidence: 99%